Structure Evolution of Oligomer Fused‐Ring Electron Acceptors toward High Efficiency of As‐Cast Polymer Solar Cells. Issue 18 (4th July 2016) - Lin, Yuze; Li, Tengfei; Zhao, Fuwen; Han, Lei; Wang, Zaiyu; Wu, Yang; He, Qiao; Wang, Jiayu; Huo, Lijun; Sun, Yanming; Wang, Chunru; Ma, Wei; et al.
Abstract : The structure evolution of oligomer fused‐ring electron acceptors (FREAs) toward high efficiency of as‐cast polymer solar cells (PSCs) is reported. First, a series of FREAs (IC‐(1‐3)IDT‐IC) based on indacenodithiophene (IDT) oligomers as cores are designed and synthesized, effects of IDT number (1–3) on their basic optical and electronic properties are investigated, and more importantly, the relationship between device performance of as‐cast PSCs and donor(D)/acceptor(A) matching (absorption, energy level, morphology, and charge transport) of IC‐(1‐3)IDT‐IC acceptors and two representative polymer donors, PTB7‐Th and PDBT‐T1 is surveyed. Then, the most promising D/A system (PDBT‐T1/IC‐1IDT‐IC) with the best D/A harmony among the six D/A combinations, which yields a power conversion efficiency (PCE) of 7.39%, is found. Finally, changing the side‐chains in IC‐1IDT‐IC from alkylphenyl to alkyl enhances the PCE from 7.39% to 9.20%. Abstract : A series of fused‐ring electron acceptors (FREAs) based on indacenodithiophene (IDT) oligomers as cores are designed and synthesized, and effects of IDT number (1–3) on their basic optical and electronic properties are investigated. High‐performance as‐cast polymer solar cells based on FREAs with power conversion efficiency as high as 9.2% are achieved through structure evolution of oligomer FREAs.